Effect of UV Irradiation and Heat Treatment on the Surface Potential Distribution of Monolayer WS2 on SiO2/Si and Au Substrates. Issue 2 (27th November 2017) - Han, Weipeng; Qi, Junjie; Li, Feng; Xu, Minxuan; Bai, Fan; Fang, Youyin; Liu, Xinxin; Zhang, Yue
Abstract: The surface potential is relevant to work function and Fermi level of materials, which is of great significance to the research of charge transport, carrier concentration, and nanodevices design. Here the effect of UV illumination and heat treatment on the surface potential distribution of chemical vapor deposition grown monolayer WS2 on SiO2 /Si and Au substrates is studied statistically. The experimental observation indicates that with the increase in light intensity, the surface potential of WS2 decreases on SiO2 /Si substrate, while increases on Au substrate. Heat treatment is introduced to tuning the surface potential of monolayer WS2, resulting in the surface potential of WS2 on SiO2 /Si substrate decrease and increase on Au substrate after annealing, respectively. The mechanism of the observed phenomenon is discussed in terms of the surface modification of the adsorption/desorption of charges on surface, photoinduced carriers, and charge transfer. This study provides a significant insight into the surface properties and can help optimize the performance of electronic and photonic devices. Abstract : The effect of ultraviolet illumination and heat treatment on the surface potential of monolayer WS2 on SiO2 /Si and Au substrates is investigated. With increasing light intensity, the surface potential of WS2 decreases on SiO2 /Si substrate, while increase on Au substrate. Furthermore, the surface potential of WS2 decreases on SiO2 /Si substrate and increases on Au substrate after annealing, respectively.